1995
DOI: 10.1002/jrs.1250260805
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman studies of heterocyclic aromatic compounds showing ultrafast intramolecular proton transfer

Abstract: Resonance Raman spectra of the three isoelectronic proton transfer systems 2(2'-hydroxy-S-methylphenyl)-benzotriazole (TIN), 2-(2'-hydroxyphenyl)benzothiazole (HBT) and 2-(2'-bydroxyphenyl)benzoxazole (HBO) were measured with excitation in the range of the S o S , absorption band of the enol tautomers. In each compound, about 15 modes in the wavenumber range between 120 and 1650 cm-' show a strong coupling to the electronic transition. In TIN and HBT, combination tones of the strongest mode below 500 cm-' and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 8 publications
4
34
0
Order By: Relevance
“…and enhanced intensities in combination bands would signal modes central to the exchange process. [55][56][57] We hope to present such an analysis for this and certain members of the SA family in a later publication.…”
Section: Discussionmentioning
confidence: 97%
“…and enhanced intensities in combination bands would signal modes central to the exchange process. [55][56][57] We hope to present such an analysis for this and certain members of the SA family in a later publication.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, combination modes of the strongest band below 500 cm 1 and the vibrations at higher wavenumbers could also be observed in two of the systems considered. 18 1-Hydroxy-2-acetonaphthone (HAN) is an extremely photostable intramolecular hydrogen bonded system used in polymer protection. 21 Several spectroscopic studies have been reported in order to discern the photophysics of HAN.…”
Section: Introductionmentioning
confidence: 99%
“…These three bands involve CÀ C stretching modes and notably the biaryl central CÀC bond. [21] The displacement of the above Raman lines is attributed to the electronic reorganization of the molecule, as expected to occur during the tautomerization.…”
mentioning
confidence: 95%